Augmentation of IL-6 production contributes to development of gestational diabetes mellitus: An Indian study. Issue 2 (March 2019) - Siddiqui, Samreen; Waghdhare, Swati; Goel, Chhavi; Panda, Manju; Soneja, Hemi; Sundar, Jayasree; Banerjee, Meenakshi; Jha, Sujeet; Dubey, Shweta
Abstract: Aim: Inflammatory mediators like interleukin-6 (IL-6) and acute phase protein like C-reactive protein (CRP) are supposed to contribute to development of GDM, however clinical data supporting this hypothesis is limited. This study was designed to analyze the association of IL-6 and CRP with development of GDM in Indian females. Methods: This case control study included pregnant women diagnosed as GDM (n = 53) and those having normal glucose tolerance (n = 50). Serum levels of IL-6 and CRP were analysed and correlated with various clinical parameters. Results: Serum IL-6 levels were significantly high ( p < 0.05) in GDM females as compared to control females. IL-6 levels correlated with pre-pregnancy body mass index (BMI), fasting blood sugar (FBS) and postprandial sugar (PPBS). Unlike IL-6, CRP levels did not show significant differences between GDM and control females. However, positive correlation of CRP levels with BMI, FBS and PPBS was observed. Conclusion: High IL-6 levels in gestational diabetes may indicate a possible role for inflammation in pathophysiology of GDM.